Detecting Beef Tallow adulteration in Palm Oil with NIR Spectroscopy and Chemometrics Analysis - Abdul Khir, Mohd Fared (International Journal of Integrated Engineering, 2018)
The NIR spectroscopy combined with chemometrics analysis has started to gain interest in the food industry for its rapid and non-destructive advantage. We report our result in investigating the capability of the NIR spectroscopy and chemometrics analysis in classifying pure palm oil samples from the one adulterated with beef tallow. The result analyzed using the open source R software has shown that the adulterated palm oil samples with adulteration of 0.5 % and above were correctly classified